2011
DOI: 10.1017/s0261444810000509
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of working memory in L2 learning

Abstract: This article reviews research on working memory (WM) and its use in second language (L2) acquisition research. Recent developments in the model and issues surrounding the operationalization of the construct itself are presented, followed by a discussion of various methods of measuring WM. These methods include word and digit span tasks, reading, listening and speaking span tasks. We next outline the role proposed for WM in explaining individual differences in L2 learning processes and outcomes, including sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
173
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(195 citation statements)
references
References 111 publications
7
173
0
7
Order By: Relevance
“…It hence is considered that the 'temporary storage and manipulation of information that is assumed to be necessary for a wide range of complex cognitive activities', such as foreign language learning, is entailed in WM (Baddeley, 2003, p. 189). Baddeley's model of WM consists of several components, of which previous research (Juffs & Harrington, 2011;Linck, Osthus, Koeth, & Bunting, 2014) has identified two as rather central to L2 acquisition: the phonological loop and the central executive; the former allows for language learning, forms the basis of memorising linguistic material and is responsible for the temporary retention and processing of phonological information, while the latter directs attentional processes (Baddeley, 2002). Many scholars thus consider WM as the most central and essential factor affecting foreign language aptitude, whereas some even claim that it has potential to replace the whole aptitude construct as such.…”
Section: Working Memory and Phonetic Language Aptitudementioning
confidence: 99%
“…It hence is considered that the 'temporary storage and manipulation of information that is assumed to be necessary for a wide range of complex cognitive activities', such as foreign language learning, is entailed in WM (Baddeley, 2003, p. 189). Baddeley's model of WM consists of several components, of which previous research (Juffs & Harrington, 2011;Linck, Osthus, Koeth, & Bunting, 2014) has identified two as rather central to L2 acquisition: the phonological loop and the central executive; the former allows for language learning, forms the basis of memorising linguistic material and is responsible for the temporary retention and processing of phonological information, while the latter directs attentional processes (Baddeley, 2002). Many scholars thus consider WM as the most central and essential factor affecting foreign language aptitude, whereas some even claim that it has potential to replace the whole aptitude construct as such.…”
Section: Working Memory and Phonetic Language Aptitudementioning
confidence: 99%
“…In the current research, one point was allocated to each recalled item. This method of scoring is supported by the most recent research (Juffs & Harrington, 2011) where it is argued to provide "a finer discrimination between individuals and be more reliable" (p. 144). To control any recency effect (Baddeley & Hitch, 1993), no points were given to the targets in math problems appearing in final positions in sets if they were recalled first.…”
Section: General Discussion and Conclusionmentioning
confidence: 80%
“…5, No. 11;2012 1992; Lesser, 2007;Walter, 2004). Finally, the results of this study suggest that the newly developed test is reliable enough to be used in language-specific and cross language studies for the measurement of working memoy capacity.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations